Rapidly progressive anti-GBM disease secondary to long-standing rheumatoid arthritis: a case report and literature review - Li, Ji; Zhang, Jing; Li, Sheng-Guang; Guo, Qian; Xu, Jing; Zhang, Lina; Zou, Yadan; Long, Ting; Yu, Ruohan; Zhang, Yanfeng (Frontiers in Immunology, 2025)
BackgroundLong-standing rheumatoid arthritis (RA) complicated by anti–glomerular basement membrane (anti-GBM) disease is exceptionally rare.CaseA 71-year-old man with long-standing seropositive RA developed a rapidly progressive glomerulonephritis due to anti-GBM disease, without any known drug triggers. Despite plasmapheresis (therapeutic plasma exchange), corticosteroids, and low-dose cyclophosphamide, he remained dialysis-dependent; RA activity was subsequently controlled with tocilizumab. Complications included Stenotrophomonas maltophilia pneumonia, COVID-19 and cytomegalovirus infection, and he died of pneumonia eight months after diagnosis.ConclusionThis case highlights the need for early serological testing for anti-GBM disease in RA patients with unexplained hematuria/proteinuria and for immunosuppressive therapy mindful of infection risk. Additionally, our literature review identified only ten reported cases of RA with anti-GBM disease, highlighting the rarity of this condition.